Discursive strategies unveiled: exploring Arab and Western media narratives on Arab women - Bushra Khalaf Edam,; Ashinida Aladdin,; Azianura Hani Shaari, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study emerges against the backdrop of increasing global interest in gender representation, focusing on the portrayal of Arab women in media narratives across both Arab and Western contexts. It critically examines the discursive strategies used in the representation of Arab women in Arab and Western media. It employs Reisigl and Wodak's Discourse-Historical Approach as a theoretical framework for data analysis. Four newspapers: Washington Post, Daily Mail, Arab News, and Gulf Times were selected for this study where a total of 40 news discourses were analysed, with ten news discourses from each newspaper, to reveal how Arab and Western media narratives shape public perceptions and contribute to the discourse on Arab women's rights and societal roles. The findings reveal that Arab newspapers primarily highlight themes of empowerment and societal participation, aligning with national modernization efforts. Their portrayal is largely positive, emphasizing the achievements of Arab women and their significant roles in traditionally male-dominated sectors. On the other hand, Western newspapers present a broader spectrum of narratives. For instance, the Washington Post provides a balanced view that acknowledges both progress and ongoing challenges, while the Daily Mail focuses on sensationalism, emphasizing persecution and cultural conflicts, thus potentially reinforcing stereotypes and advocating Western norms of gender equality. It is revealed that while Arab media aim to project a progressive image of Arab women and align with broader governmental reforms, Western media often highlight negative aspects, influencing international perspectives and policy debates. The study underscores the significant impact of these media portrayals on public opinion and contributes to a deeper understanding of the media's role in shaping and challenging the narratives surrounding Arab women, highlighting areas for further scholarly exploration and policy consideration.